THE URGENCY OF MILITARY INTUITION LEADERSHIP TRANSFORMATION IN THE DIGITAL ERA - Fitry Taufiq Sahary; K.P.Suharyono S.Hadiningrat (Yayasan Inspirasi Merah Putih Indonesia, 2024)
Leaders in an organization/institution/government are role models who move their members to perform their best to achieve common goals. On the shoulders of a leader or commander is charged with the important task of controlling all resources owned. Leadership style is very dynamic and must be able to provide future direction in order to maintain existence and sustainability. In the military, commanders are required to advance teams and organizations with various efforts, including applying intuitive leadership adapted to advances in information and communication technology (digital technology). This research design is descriptive qualitative to find and describe research variables in a narrative (non-numerical) manner. The selection of a qualitative research approach was carried out on the basis of the specifications of the research subjects and to obtain in-depth information about the research variables. The results obtained that Military Intuition Leadership has an important role in strategic decision making to improve the ability of military organizations to face various challenges and assignments that are fast and complex, especially in the digital era. So that the transformation of intuition military leadership is needed in the digital era so that the information / data obtained is more accurate and the process is faster. In this case, intuitive leadership involves the use of insight, instinct, and intuitive judgment based on experience, deep understanding, and holistic thinking. In its application, it is necessary to consider carefully, hone the ability to read what is happening, analyze the possibilities that occur in the future is an advantage that a leader must have because of his experience and intuition. It is recommended that commanders in the military train their intuitive skills to be more effective and consider the dangers of using overconfidence in decision-making.